Implementation of the One Family One Graduate Scholarship Program in Baznas of South Sumatera Province - Wiwik Oktarina; Fitri Oviyanti; Nazaruddin Nazaruddin (Budapest International Research and Critics University, 2022)
The background of this research stems from the researcher's interest in the privileges of zakat management institutions. The privilege is none other than that zakat management institutions are able to manage zakat effectively, especially in terms of maintaining the trust of the muzakki and are able to channel these funds through various programs, one of which is the Smart Sumsel program. Therefore, the researcher conducted a research entitled